1917 Or. Gen. and Special Laws 807, ch. 377, § 7 - (:unkn) unknown (My University, 1917)
Prohibited the attempted use, or the carry and possession with the intent to use, any dagger, dirk, dangerous knife, razor, stiletto, loaded pistol, revolver, or other firearm, or any instrument or weapon of the kind commonly known as a blackjack, slungshot, billy, sandclub, sandbag, metal knuckles, bomb, bombshell, or any other "dangerous or deadly weapon." Punishable by a fine of $50-500 or imprisonment for 1-6 months.
Keywords: CARRY - INTENT TO COMMIT CRIME